P3-S1.22 Evaluation of performance of six commercial assays for detection of characterised isolates of Neisseria gonorrhoeae and other Neisseria spp. (10th July 2011) - Tabrizi, S; Unemo, M; Limnios, A; Hjelmevoll, S O; Garland, S; Tapsall, J
Abstract : Background: Molecular detection of Neisseria gonorrhoeae in urogenital samples is now routinely conducted in many diagnostic laboratories with the demand also expanding to testing of extragenital samples. Testing of extragenital samples poses a challenge as it may result in false positive results due to cross-reaction with commensal Neisseria spp. and N meningitidis . Adequate evaluation of molecular assays is essential prior to expanding utilisation of the assays to such specimens. Method: This study aimed to examine 450 characterised clinical isolates comprising of 216 N gonorrhoeae and 234 other Neisseria spp. and closely related bacteria from various geographical regions worldwide with six commercial assays including GenProbe APTIMA Combo 2 and APTIMA GC; Roche COBAS Amplicor CT/NG and COBAS 4800 CT/NG; BD ProbeTec GC Qx Amplified DNA Assay and Abbott RealTime CT/NG. Results: Among 216 N gonorrhoeae isolates included in the study, all assays except COBAS Amplicor where four (1.9%) gonococcus isolates were not detected, showed a positive result with all N gonorrhoeae isolates. Among 234 Neisseria spp. evaluated, initial results showed all assays evaluated to display cross reaction with non-gonococcal Neisseria isolates. COBAS Amplicor and ProbeTec showed highest number of false positives, detecting 33 (14.1%) and 26 (11%) non-gonococcal Neisseria isolates respectively. Abbott RealTime, APTIMA Combo and APTIMA GC, and Roche COBAS 4800 showed initially low level of cross reaction, that is, detected 2 (1%), 5 (2.1%), 4 (1.7%) and 2 (1%) of the isolates respectively. When retested by the company using a fresh culture, none of these nine isolates showed cross reaction with the respective assays. Conclusion: COBAS Amplicor and ProbeTec displayed highest number of false positives among assays evaluated, with the remaining assays only showing sporadic low level false positivity. Especially when examining extragenital specimens, supplementary testing for all assays and platforms remains recommended.